The big secret for the small investor : a new route to long-term investment success - Greenblatt, Joel. (New York: Crown Business, 2011)
oel Greenblatt outlines simple strategies investors can use to build a strong stock portfolio, increase their returns, and master the art of investing.
Includes bibliographical references
Keywords: Stocks; Investments; Portfolio management